2016
DOI: 10.1016/j.pharep.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific influences of chronic administration of the fatty acid amide hydrolase inhibitor URB597 on cardiovascular parameters and organ hypertrophy in DOCA-salt hypertensive rats

Abstract: Two weeks of URB597 administration to DOCA-salt hypertensive rats caused an age-specific reduction in BP, HR and cardiac and renal hypertrophy and did not affect the body weight, and water and food intake. Thus, caution should be taken during studies of FAAH inhibitors because of their potential age-specific effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Simultaneously, the hypertensive rats were given 1% NaCl in the drinking water with concomitant injections of DOCA (25 mg/kg [18-21] in 0.4 ml/kg DMF). After 4 weeks, half of the normotensive and half of the hypertensive animals were injected with URB597 (1mg/ml/kg) twice a day for the next 2 weeks [12, 22, 23]. At the same time the rest of rats received URB597 solvent – DMSO (1 ml/kg; Tween 80 and 0.9% NaCl (1: 2:7)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, the hypertensive rats were given 1% NaCl in the drinking water with concomitant injections of DOCA (25 mg/kg [18-21] in 0.4 ml/kg DMF). After 4 weeks, half of the normotensive and half of the hypertensive animals were injected with URB597 (1mg/ml/kg) twice a day for the next 2 weeks [12, 22, 23]. At the same time the rest of rats received URB597 solvent – DMSO (1 ml/kg; Tween 80 and 0.9% NaCl (1: 2:7)).…”
Section: Methodsmentioning
confidence: 99%
“…It should be mentioned that fatty acid amide hydrolase (FAAH) is an enzyme, which is responsible for AEA degradation and, therefore, determines endocannabinoids activity in the tissues [10]. Interestingly, studies have shown that both, acute and chronic pharmacological FAAH inhibition by (30-(aminocarbonyl)[1, 10-biphenyl]-3-yl)-cyclohexylcarbamate (URB597) administration normalized elevated blood pressure [11, 12]. Since the ECS controls energy homeostasis [13] we wanted to determine whether decreased FAAH activity would have an impact on cardiac metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in various forms of hypertension, the eCB system becomes tonically active. This occurs by enhancing the vasorelaxant responses to eCBs, changes in plasma eCB concentration or alterations in the vascular expression of eCB system components, including up‐regulation of CB 1 receptors . It is worth mentioning that more research concerns the possible role of the eCB system in cardiovascular regulation in hypertension …”
Section: Introductionmentioning
confidence: 99%
“…This occurs by enhancing the vasorelaxant responses to eCBs, changes in plasma eCB concentration or alterations in the vascular expression of eCB system components, including up-regulation of CB 1 receptors. [3][4][5][6][7] It is worth mentioning that more research concerns the possible role of the eCB system in cardiovascular regulation in hypertension. [3,6,8] Cannabinoid signalling through the CB 1 -sensitive pathway can cause vasorelaxation via activation of nitric oxide synthase, increase in cyclic guanosine monophosphate and opening of potassium channels which causes membrane hyperpolarization, [5,9] see also Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, URB597 reduced cardiac and renal hypertrophy in younger and hypertrophy of aorta and coronary vessels (but not mesenteric artery) in older DOCA‐salt rats. However, it did not diminish organ hypertrophy in SHR as well as cardiomyocyte dimension and density of coronary blood vessels in DOCA‐salt animals (Toczek et al ., and unpublished; Polak et al ., ).…”
Section: Effects Of Chronic Cannabinoid Administration On Cardiovascumentioning
confidence: 97%